Α4β1 integrin promotes accumulation of tissue‐resident memory CD8+ T cells in salivary glands. Issue 2 (7th December 2016) - Woyciechowski, Sandra; Hofmann, Maike; Pircher, Hanspeter
Abstract : Tissue‐resident memory CD8 + T cells (TRM ) provide local immunity. Immune stimuli such as lymphocytic choriomeningitis virus infection or poly(I:C) treatment promote accumulation of CD8 + TRM cells in salivary glands in an α4 β1 integrin‐dependent manner. These stimuli increase α4 β1 integrin in activated T cells and VCAM‐1 in salivary gland endothelium. Abstract : The salivary glands (SGs) of virus‐immune mice contain substantial numbers of tissue‐resident memory CD8 + T cells (TRM cells) that can provide immunity to local infections. Integrins regulate entry of activated T cells into nonlymphoid tissues but the molecules that mediate migration of virus‐specific CD8 + T cells to the SGs have not yet been defined. Here, we found that polyinosinic‐polycytidylic acid (poly(I:C)) strongly promoted the accumulation of P14 TCR‐transgenic CD8 + TRM cells in SGs in an α4 β1 integrin‐dependent manner. After infection with lymphocytic choriomeningitis virus, accumulation of P14 TRM cells in SGs and intestine but not in kidney was also α4 integrin dependent. Blockade of α4 β7 by monoclonal antibodies (mAbs) inhibited lymphocytic choriomeningitis virus‐induced accumulation of P14 TRM cells in the intestine but not in SGs. In conclusion, our data reveal that α4 β1 integrin mediates CD8 + TRM accumulation in SGs and that poly(I:C) can be used to direct activated CD8 + T cells to this organ.